Weighted weak-type iterated and bilinear Hardy inequalities - García García, V.; Ortega-Salvador, Pedro (Elsevier, 2023)
We characterize the good weights for a certain weighted weak-type iterated Hardy inequality to hold. As a consequence, we get the characterizations of some weighted weak-type bilinear Hardy inequalities.
Keywords: Desigualdades (Matemáticas); Análisis matemático; Bilinear Hardy inequalities; Iterated Hardy inequalities; Weighted weak-type inequalities; Weighted inequalities; Weights